An Ayurvedic Review on Poly-Cystic Ovarian Disease (International Journal of Ayurveda and Pharma Research, 2022)
PCOD is the most common endocrine disorder in women of reproductive age group, affecting 5% to 10% of women exhibiting, the full blown syndrome of hyperandrogenism, chronic anovulation and polycystic ovaries. PCOD is a disease which is related to the cystic changes in the ovary. It is the most common cause of Menstrual Irregularities, Obesity, anovulatory infertility and hyperandrogenism, etc. PCOD are not compiled as a disease or syndrome in Ayurveda, most of them have been described as symptoms of separate diseases or conditions. Ayurvedic management principles Samshodhana, Agneya dravya, Nidan parivarjana as well as modern treatment describe here. The present article is an attempt to highlighting on details of Ayurvedic review on poly cystic ovarian diseases.